An integrated framework for ship structural optimisation in contract design phase - Abbas Bayatfar (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding, 2019)
This paper demonstrates the implementation of an integrated workflow for the finite element-based structural assessment/optimization of a 3D midship segment of RoPax vessel within the contract design phase. Commercial software such as AVEVA Marine®, ANSYS® and modeFRONTIER® and newly developed in-house tools/modules have been integrated under an automated iterative routine. The structural optimisation carried out with an aim to reduce the structural weight of the ship with least value for vertical centre of gravity. Constraints implemented in the optimization include relevant BV rules and shipyard requirements.The work is performed within the framework of European Union’s HOLISHIP (2016-2020) project.